Associations of Human Milk Oligosaccharides and Bioactive Proteins with Infant Morbidity and Inflammation in Malawian Mother-Infant Dyads. Issue 5 (29th April 2021) - Jorgensen, Josh M; Young, Rebecca; Ashorn, Per; Ashorn, Ulla; Chaima, David; Davis, Jasmine C C; Goonatilleke, Elisha; Kumwenda, Chiza; Lebrilla, Carlito B; Maleta, Kenneth; Sadalaki, John; Totten, Sarah M; et al.
ABSTRACT: Background: Human milk oligosaccharides (HMOs) and bioactive proteins likely benefit infant health, but information on these relations is sparse. Objectives: We aimed to examine associations of milk content of HMOs and bioactive proteins with incidence and longitudinal prevalence of infant morbidity (any illness, fever, diarrhea, acute respiratory infection, and loss of appetite) and markers of inflammation [C-reactive protein (CRP) and α-1-acid glycoprotein (AGP)]. These are secondary analyses of a randomized controlled trial. Methods: Breast milk samples at 6 mo postpartum ( n   = 659) were analyzed to quantify absolute abundance of HMOs, relative abundance of fucosylated HMOs, sialylated HMOs, and 51 individual HMOs, and concentrations of 6 bioactive proteins (lactalbumin, lactoferrin, lysozyme, antitrypsin, IgA, and osteopontin). We examined associations of these constituents with infant morbidity from 6 to 7 and 6 to 12 mo, and CRP and AGP at 6 and 18 mo, considering maternal secretor status [presence or absence of the functional enzyme encoded by the fucosyltransferase 2 gene ( FUT2 ) ] and adjusting for covariates and multiple hypothesis testing. Results: In secretors there were positive associations between total HMOs and longitudinal prevalence of fever ( P  = 0.032), between fucosylated HMOs and incidence of diarrhea ( P  = 0.026), and between lactoferrin and elevated CRP at 18 mo ( P  = 0.011). In nonsecretors, there were inverse associations between lactoferrin and incidence of fever ( P   = 0.007), between osteopontin and longitudinal prevalence of lost appetite ( P   = 0.038), and between fucosylated HMOs and incidence of diarrhea ( P  = 0.025), lost appetite ( P  = 0.019), and concentrations of AGP and CRP at 6 mo ( P  = 0.001 and 0.010); and positive associations between total HMOs and incidence of lost appetite ( P  = 0.024) and elevated CRP at 18 mo ( P   = 0.026), between lactalbumin and incidence of diarrhea ( P  = 0.006), and between lactoferrin and elevated CRP at 18 mo ( P  = 0.015). Conclusions: Certain HMOs and bioactive proteins were associated with infant morbidity and inflammation, particularly in nonsecretors. Further research is needed to elucidate the causality of these relations. This trial was registered at clinicaltrials.gov as NCT01239693.